THE IMPORTANCE OF THE AUDIO-LINGUAL METHOD IN TEACHING ENGLISH - Urazmatova Madina (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Teaching English as a foreign language has seen numerous methodological shifts over the years, but some traditional approaches continue to hold pedagogical value. Among these, the Audio-Lingual Method (ALM) remains one of the most influential techniques in fostering accurate spoken English, particularly at the beginner and intermediate levels. Despite being introduced in the mid-20th century, its emphasis on spoken patterns, pronunciation, and grammar structures ensures its ongoing relevance in modern language classrooms, especially in contexts where communicative confidence is still developing.